SYNDROMES OF KETOSIS-PRONE DIABETES - BALASUBRAMANYAM, ASHOK (Trans Am Clin Climatol Assoc, 2019)
Ketosis-prone diabetes (KPD) is a heterogeneous condition characterized by patients who present with diabetic ketoacidosis but lack the phenotype of autoimmune type 1 diabetes. Here I review progress in our understanding of KPD and its place in the expanding universe of “atypical diabetes.” I focus on investigations of our collaborative research group at Baylor College of Medicine and the University of Washington using a longitudinally followed, heterogeneous, multiethnic cohort of KPD patients. We have identified clinically and pathophysiologically distinct KPD subgroups, separable by the presence or absence of islet autoimmunity and the presence or absence of beta cell functional reserve. The resulting “Aß” classification of KPD accurately predicts long-term glycemic control and insulin dependence. I describe key characteristics of the KPD subgroups, their natural histories, and our investigations into their immunologic, genetic, and metabolic etiologies. These studies serve as a paradigm for the investigation of atypical forms of diabetes.